Vpliv glivnih in rastlinskih sekundarnih metabolitov na verižno reakcijo s polimerazo (PCR) - Thaler, Nejc (Acta silvae et ligni, 2013)
Secondary metabolites are organic compounds that can be found in both fungi and plants, where they play an important role as defensive and signal molecules, or provide other kinds of advantage in natural selection, but are not directly involved in normal growth, development and reproduction of an organism. When working with DNA techniques, it is the secondary metabolites that most often affect the efficiency of polymerase chain reaction (PCR), either by hindering cell lysis, causing decomposition of nucleic acids or by direct inhibition of DNA-polymerase or reverse transcriptase amplification. The main limiting factor in the application of the PCR technique in routine diagnosis is the preparation of good quality nucleic acids isolates, free of PCR inhibitors. This is especially true in the case of woody plants (Minafra et al., 1992) and soil samples (Tsai and Olson, 1991). Most standard nucleic acids extraction procedures do not always remove contaminating plant polysaccharides or polyphenolic compounds, which can have direct inhibitory effects on subsequent PCR amplification (Demeke and Adams, 1992). Attempts to overcome these limitations included the development of more elaborate nucleic acids extraction methods and PCR, which employ PCR enhancers to eliminate or attenuate the effects of inhibitors. This review is concentrated on removal or attenuation of effects of plant and fungal secondary metabolites from soil, different plant tissues and decayed wood samples due to the significance of this type of research in forestry and wood science.
Keywords: sekundarni metaboliti; izolacija DNA; pomnoževanje DNA; verižna reakcija; polimeraza; polymerase chain reaction; PCR